OR16-01 The Expression of the Homeodomain Transcription Factor SIX3 within Kisspeptin Neurons Is Necessary for Reproduction in Mice - Lavalle, Shanna N (J Endocr Soc, 2020)
The homeodomain transcription factor SIX3 is necessary for normal reproductive processes in mice. The loss of a single allele results in haploinsufficient phenotypes that are reflective of individuals with Kallmann Syndrome, such as hypogonadism, reduced GnRH neurons, and anosmia. Six3 heterozygous mice have reproductive impairments including an increased time to first litter, increased estrous cycle lengths in females, and fewer litters in males compared to wildtype controls. Prior studies found that deleting SIX3 specifically from GnRH neurons did not recapitulate the same phenotypes produced from a global knockout of the Six3 allele and imposed no reproductive abnormalities. This suggests that the role of SIX3 in reproduction is due to SIX3 populations outside of GnRH neurons. Using qPCR and RNA-seq, we have verified that Six3 is expressed in arcuate nucleus (ARC) and anteroventral periventricular nucleus (AVPV) populations of kisspeptin neurons and can regulate the kisspeptin promoter in vitro. This led us to hypothesize that SIX3 in kisspeptin neurons is required for Kiss1 regulation and maximal fertility. We selectively deleted Six3 from kisspeptin neurons by crossing a Six3-floxed mouse with a Kiss1-Cre mouse to produce Six3 flox/flox; Kiss1-Cre positive mice (cKO) and Six3 flox/flox, Kiss-Cre negative littermates (controls). In female mice, we found that the loss of SIX3 from kisspeptin neurons disrupted the estrous cycle and reduced fertility. Compared to controls, cKO mice had fewer cycles in a 16-day period (0.38 vs 1.44; p=0.004; n=8-9), and spent a greater percentage of time in diestrus (80.5 vs 61.8; p=0.002; n=8-9) and a smaller percentage of time in estrus (15.6 vs 29.2; p=0.030; n=8-9). The loss of kisspeptin-specific SIX3 also resulted in reduced fecundity, with the cKO female mice having fewer pups within 90 days (15.0 vs 34.4; p=0.048; n=5-6) compared to controls. In addition to its importance in female mice, kisspeptin-specific SIX3 also plays a role in male fertility. We found that male cKO mice had reduced motile sperm (52.2% vs 72.5%; p=0.012; n=7-9) compared to controls. We also assayed levels of Kiss1 mRNA in the male arcuate nucleus and observed decreased Kiss1 levels compared to controls (0.34 vs 1.01; p=0.042; n=3-4). These results support our hypothesis that SIX3 in kisspeptin neurons is necessary for critical reproductive processes in both females and males, including progression through the estrous cycle, fecundity, and sperm motility, potentially through Kiss1 regulation.